DAMPAK KERJASAMA PERDAGANGAN SENJATA AMERIKA SERIKAT TERHADAP PENINGKATAN EKONOMI TAIWAN - Ramadhani, Fandra; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research explains the Impact of United States arms trade cooperation against Taiwan economic improvement. The consequences of the Korean war brought the United States into an agreement with the Taiwanese government of the Mutual Defense Treaty (1954) to assist Taiwan in tackling the threat of Tiongkok. Since then the United States has provided much economic and military aid to Taiwan for defense and security and the future of Taiwan's development. Over time the United States supplied large quantities of military equipment to Taiwan in anticipation of Tiongkok. The method used in this research is descriptive, qualitative. The data obtained comes from books, journals, theses, articles, internet sites and other sources related to research. The focus of this research is on whether the impact of US and Taiwan arms trade cooperation on Taiwan's economy. The perspective I use is a neo-liberalist perspective, the theory of international political economy. The impact of the US arms trade cooperation with Taiwan on an increasing investment that could allow Taiwan's industry in developing weapons, the renewal of the armaments. The Americans also provide Taiwan with enough military weapons and communication devices. Gun sales are an important component in maintaining peace and stability in cross-strait relations and across the region.Keywords: arms trade, defense equipment, Taiwan, economic